Phylogenetics and systematics of the subfamilies Cheirurinae and Deiphoninae (Trilobita) - Francesc Pérez-Peris; Jonathan M. Adrain; Allison C. Daley (Swiss Journal of Palaeontology)
Abstract Cheiruridae is one of the most diverse families of trilobites known from the Ordovician with 453 species assigned. Within Cheiruridae eight subfamilies (Acanthoparyphinae, Cheirurinae, “Cyrtometopinae”, Deiphoninae, Eccoptochilinae, Heliomerinae, Pilekiinae, and Sphaerexochinae) have historically been recognised. Insights about the evolution of the family and the relationships within and between subfamilies have been published. However larger scale phylogenetic hypotheses are needed in order to explore the monophyly, the basal structure, the deep nodes and the relationships of the subfamilies. Cheirurinae, Deiphoninae and “Cyrtometopinae” have historically been defined by various morphological features (e.g., anteroposterior constriction of the thoracic pleura, pleural furrow morphology, pygidial morphology) that differentiate them from the rest of Cheiruridae. However, the phylogenetic status of “Cyrtometopinae” is unclear owing to a lack of obvious synapomorphies. Here, we present phylogenetic analyses of Cheirurinae, Deiphoninae, and “Cyrtometopinae”. The results indicate that both Cheirurinae and Deiphoninae are monophyletic. “Cyrtometopines” are resolved as a paraphyletic grade at the base of Deiphoninae and Cyrtometopinae should be considered a junior subjective synonym of Deiphoninae. The new phylogenetic hypothesis reveals that paedomorphosis plays an important role in the evolution of Deiphoninae. Within Cheirurinae two major clades are identified, the ‘Ceraurus-like’ clade and the ‘Ceraurinella-like’ clade.